2020
DOI: 10.1159/000509916
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial Block Predicts Atrial Fibrillation and Total Mortality in Patients with Cardiac Resynchronization Therapy

Abstract: Background: Interatrial block (IAB) and abnormal P-wave terminal force in lead V1 (PTFV1) are electrocardiographic (ECG) abnormalities that have been shown to be associated with new-onset atrial fibrillation (AF) and death. However, their prognostic importance has not been proven in cardiac resynchronization therapy (CRT) recipients. Objective: To assess if IAB and abnormal PTFV1 are associated with new-onset AF or death in CRT recipients. Methods: CRT recipients with sinus rhythm ECG at CRT implantation and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“… 31 A study of HF patients receiving cardiac resynchronization therapy devices found that abnormal P‐wave terminal force in V1 and PWD ≥ 120 ms significantly predicted new‐onset AF and all‐cause mortality. 32 Moreover, prolongations in amplified PWDs were predictive of new‐onset AF in patients with HF with preserved ejection fraction. 33 Similar findings have been observed in the context of HF with reduced ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 A study of HF patients receiving cardiac resynchronization therapy devices found that abnormal P‐wave terminal force in V1 and PWD ≥ 120 ms significantly predicted new‐onset AF and all‐cause mortality. 32 Moreover, prolongations in amplified PWDs were predictive of new‐onset AF in patients with HF with preserved ejection fraction. 33 Similar findings have been observed in the context of HF with reduced ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, prolonged PWDs ≥120 ms predicted new‐onset AF and all‐cause mortality, whereas abnormal P‐wave terminal force in V1 predicted stroke 31 . A study of HF patients receiving cardiac resynchronization therapy devices found that abnormal P‐wave terminal force in V1 and PWD ≥ 120 ms significantly predicted new‐onset AF and all‐cause mortality 32 . Moreover, prolongations in amplified PWDs were predictive of new‐onset AF in patients with HF with preserved ejection fraction 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We also observed an association between aIAB and incident HF in our study. aIAB is a risk factor for AF, stroke, cognitive impairment, and mortality ( 40 42 ). Advanced age, hypertension, and coronary artery disease (CAD) are risk factors for aIAB development and are pathophysiologically linked to fibrotic atrial cardiomyopathy (FAC) and reduced LA strain indexes ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies demonstrated that advanced IAB was associated with CHADS 2 score, which was also a common independent predictor of IAB development and ischemic stroke ( Wu et al, 2018 ). Furthermore, a recent study demonstrated that advanced IAB could predict all-cause mortality in ischemic stroke survivors with and without additional cardiovascular comorbidities ( Baturova et al, 2019 ; Jacobsson et al, 2020 ; Prasitlumkum et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%